Complete genome sequence of Nguyenibacter sp. L1, a phosphate solubilizing bacterium isolated from Lespedeza bicolor rhizosphere - Li, Xiao Li; Lv, Xin Yang; Ji, Jun Bin; Wang, Wei Duo; Wang, Ji; Wang, Cong; He, Hai Bin; Ben, Ai Ling; Liu, Ting Li (Frontiers in Microbiology, 2023)
Phosphorus (P) deficiency is a predominant constraint on plant growth in acidified soils, largely due to the sequestration of P by toxic aluminum (Al) compounds. Indigenous phosphorus-solubilizing bacteria (PSBs) capable of mobilizing Al-P in these soils hold significant promise. A novel Al-Psolubilizing strain, Al-P Nguyenibacter sp. L1, was isolated from the rhizosphere soil of healthy Lespedeza bicolor plants indigenous to acidic terrains. However, our understanding of the genomic landscape of bacterial species within the genus Nguyenibacter remains in its infancy. To further explore its biotechnological potentialities, we sequenced the complete genome of this strain, employing an amalgamation of Oxford Nanopore ONT and Illumina sequencing platforms. The resultant genomic sequence of Nguyenibacter sp. L1 manifests as a singular, circular chromosome encompassing 4,294,433 nucleotides and displaying a GC content of 66.73%. The genome was found to host 3,820 protein-coding sequences, 12 rRNAs, and 55 tRNAs. Intriguingly, annotations derived from the eggNOG and KEGG databases indicate the presence of genes affiliated with phosphorus solubilization and nitrogen fixation, including iscU, glnA, and gltB/D associated with nitrogen fixation, and pqqBC 删除了: 3108 associated with inorganic phosphate dissolution. Several bioactive secondary metabolite genes in the genome, including pqqCDE, phytoene synthase and squalene synthase predicted by antiSMASH. Moreover, we uncovered a complete metabolic pathway for ammonia, suggesting an ammonia-affinity property inherent to Nguyenibacter sp. L1. This study verifies the nitrogen-fixing and phosphatedissolving abilities of Nguyenibacter sp. L1 at the molecular level through genetic screening and analysis. The insights gleaned from this study offer strategic guidance for future strain enhancement and establish a strong foundation for the potential incorporation of this bacterium into agricultural practices.